The social determinants of ideology: the case of neoliberalism in Southern Europe - Tsatsanis, E. (Critical Sociology, 2009)
The specific research questions that lie at the heart of this article correspond to three related but distinct areas of inquiry: a) the ideology of neoliberalism and the broad empirical question concerning its suggested status of present-day `hegemonic' ideology; b) the explanatory power of `class' with regard to questions of ideology; and c) regional patterns of popularity of neoliberal ideas in Europe, with a focus on the countries of southern Europe (Portugal, Spain, Italy, and Greece). The findings of the study reveal that: a) there are surprisingly low levels of support for neoliberal ideas across Europe; b) class (when conceptualized and operationalized more subtly) continues to be a very useful explanatory tool of relative ideological orientation; and c) social and institutional differences between northern and southern Europe are also reflected at the ideological level.